Efektivitas Penggunaan Modul Praktikum Sistematika Vertebrata pada Materi Classis Amphibia di Program Studi Pendidikan Biologi Universitas Muhammadiyah Surakarta - Ima Aryani (Universitas Sebelas Maret, 2018)
The objectives of this research was (1) to know effectiveness of the use of vertical systematic practice module to improve the learning outcomes of vertebrate systematic practice. This research was a quantitative description of research conducted in Biology Education Department of FKIP UMS. The population in this research was all students of Biology Education who took practice of Vertebrate Systematics in the academic year of 2016/2017. The sample used in this research was the students of Biology Education semester VI class B who took the practice of Vertebrata Systematics in the academic year of 2016/2017. Data analysis techniques in this study used One Group Pretest-Posttest Design. Data analysis used non parametric statistic with Wilcoxon test. After the data were tested with non parametric statistic then tested its effectiveness to know the improvement of student learning result using normalized gain score technique. The results of this study indicated that the module practice vertebrate systematic classis amphibia ˝Effective˝ used as teaching materials, module effectiveness was based on the results of N-gain calculation in terms of the increase of cognitive test results of 0.43 are categorized ˝moderate˝.